Physical and Nutritional Properties of Analog Rice Based on Modified Cassava Flour and Modified Suweg Flour - Umar Hafidz Asy'ari Hasbullah; Latifatus Surayya; Ikrar Taruna Syah (Indonesian Food and Nutrition Progress, 2022)
Analog rice can be developed from modified cassava flour (MOCAF) and modified Suweg (Amorphophallus campanulatus) flour (MSF). This research aims to study the physical and nutritional characteristics of analog rice made from a combination of MOCAF and MSF. Analog rice was formulated from both flour with MOCAF: MSF ratios (w/w), among others (100: 0), (90: 10), (80:20), (70:30), (60:40), and (50:50). The dough was printed in an extruder and dried so that it becomes analog rice. The results showed that changes in the MOCAF: MSF ratio cause significant changes to the physical characteristics and nutrients of analog rice. Interestingly, the increasing amount of MSF in the formulation causes the weight of one hundred grains, bulk density, protein, water, ash, and crude fiber in analog rice to rise. However, water absorption, color brightness, fat, and carbohydrates in analog rice was fell 54%, 17%, 23%, 4%, respectively. Therefore, analog rice produced from MOCAF and MSF can be a source of food to maintain the nation's food security.